REVIEW OF CASE LAW 5TH CHAMBER OF THE SUPREME COURT - López de Celis, José María (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
THE POSSIBILITY OF ATTENDING AND INTERVENING IN THE STATEMENTS OF THE OTHER PARTY, AS THERE ARE TWO DEFENDANTS AND THEY ARE CONSIDERED AS OPPOSING PARTIES (CO-PARTIES). Supreme Court Ruling 5th Chamber, 22 March 2023 MINOR OFFENCE PROVIDED FOR IN ARTICLE 9.4 OF THE LORDGC, CONSISTING OF "INFRINGEMENT OF THE RULES ON THE DUTY OF RESIDENCE". Supreme Court Ruling 5th Chamber, 22 March 2023 THE SUSPENSION APPROVED TO PROVIDE NOTICE OF THE AGREEMENT TO INITIATE SANCTIONING PROCEEDINGS AND TO HOLD A HEARING. Supreme Court Ruling 5th Chamber, 14 February 2023 REQUEST FOR REPORTS BY A SUPERIOR TO A SUBORDINATE, IN RELATION TO THE FUNDAMENTAL RIGHT NOT TO TESTIFY AGAINST ONESELF AND NOT TO CONFESS GUILT. Supreme Court Ruling 5th Chamber, 09 February 2023 ROLE OF THE INSTRUCTOR IN CASES INVOLVING MINOR OFFENCES. Supreme Court Ruling 5th Chamber, 26 January 2023; EXPIRATION OF PROCEEDINGS FOR MINOR OFFENCES. Supreme Court Ruling 5th Chamber, 18 January 2023 SERIOUS OFFENCE CONSISTING OF "SERIOUS DISRESPECT TOWARDS SUPERIORS, COLLEAGUES, SUBORDINATES OR CITIZENS IN THE EXERCISE OF THEIR DUTIES, AS PART OF THEIR DUTIES OR WHILE IN UNIFORM", PROVIDED FOR IN ARTICLE 8.6 OF THE LORDGC. Supreme Court Ruling 5th Chamber, 30 December 2022 “GROSS NEGLIGENCE IN THE FULFILMENT OF PROFESSIONAL OBLIGATIONS OR ORDERS RECEIVED”, PROVIDED FOR IN ARTICLE 8.33 OF THE LORDGC. Supreme Court Ruling 5th Chamber, 30 December 2022 "SERIOUS OFFENCE AS PROVIDED FOR IN ARTICLE 8.33 OF THE LORDGC “SERIOUS NEGLIGENCE IN THE FULFILMENT OF PROFESSIONAL OBLIGATIONS OR ORDERS RECEIVED”. Supreme Court Ruling 5th Chamber, 21 December 2022 SERIOUS OFFENCE OF “ANY REQUEST BASED ON FALSE ASSERTIONS", PROVIDED FOR IN ARTICLE 8.21 OF LORDGC. Supreme Court Ruling 5th Chamber, 21 December 2022 ARTICLE 7.18 OF LORDGC, CONSISTING OF “CARRYING OUT ANY ACTIVITY THAT BREACHES THE RULES ON INCOMPATIBILITIES”. Supreme Court Ruling 5th Chamber, 21 December 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.27 OF THE LORDGC, CONSISTING OF "EXCEEDING, AT THE BEGINNING OR DURING THE PROVISION OF THE SERVICE, A BLOOD ALCOHOL LEVEL OF MORE THAN 0.3 GRAMS PER LITRE OR ALCOHOL IN EXHALED AIR OF MORE THAN 0.15 MILLIGRAMS PER LITRE". Supreme Court Ruling 5th Chamber, 20 December 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.23 OF THE LORDGC, CONSISTING OF “PROVIDING SERVICE UNDER THE INFLUENCE OF NARCOTICS OR TOXIC OR PSYCHOTROPIC SUBSTANCES”. Supreme Court Ruling 5th Chamber, 24 November 2022 MINOR OFFENCE PROVIDED FOR IN ARTICLE 9.18 OF THE LORDGC, CONSISTING OF "DISRESPECT OR INATTENTIVE ANSWERS TO A SUPERIOR". Supreme Court Ruling 5th Chamber, 17 November 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.8 OF LORDGC, CONSISTING OF “BREACH OF PROFESSIONAL SECRECY”. Supreme Court Ruling 5th Chamber, 19 October 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.26 OF THE LORDGC, CONSISTING OF "COMMITTING A SERIOUS OFFENCE, HAVING A SERIOUS OFFENCE AND A VERY SERIOUS OFFENCE IN ONE’S RECORDS, WITHOUT IT BEING CANCELLED". Supreme Court Ruling 5th Chamber, 05 October 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.33 OF THE LORDGC, CONSISTING OF A “SERIOUS OFFENCE IN THE FULFILMENT OF PROFESSIONAL OBLIGATIONS”. Supreme Court Ruling 5th Chamber, 05 October 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.13 OF THE LORDGC, CONSISTING OF “COMMITTING A FRAUDULENT OFFENCE AS RECOGNISED IN A FINAL RULING, RELATED TO THE SERVICE, OR ANY OTHER OFFENCE THAT CAUSES SERIOUS DAMAGE TO THE ADMINISTRATION, CITIZENS OR LEGAL ENTITIES”. Supreme Court Ruling 5th Chamber, 21 September 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.18 OF THE LORDGC, CONSISTING OF “CARRYING OUT ANY ACTIVITY THAT BREACHES THE RULES ON INCOMPATIBILITIES”. Supreme Court Ruling 5th Chamber, 21 September 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.29 OF THE LORDGC, CONSISTING OF “CONVICTION IN A FINAL RULING OF AN INTENTIONAL CRIME, PROVIDED THAT IT DOES NOT CONSTITUTE A VERY SERIOUS CRIME". Supreme Court Ruling 5th Chamber, 21 September 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.21 OF THE LORDGC, CONSISTING OF “ANY CLAIM, REQUEST OR MANIFESTATION BASED ON FALSE ASSERTIONS”. Supreme Court Ruling 5th Chamber, 19 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.10 OF THE LORDGC, CONSISTING OF “FAILING TO APPEAR TO PROVIDE A SERVICE”. Supreme Court Ruling 5th Chamber, 14 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.18 OF THE LORDGC, CONSISTING OF “CARRYING OUT ANY ACTIVITY THAT BREACHES THE RULES ON INCOMPATIBILITIES”. Supreme Court Ruling 5th Chamber, 13 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.13 OF THE LORDGC, CONSISTING OF “COMMITTING A FRAUDULENT OFFENCE REFLECTED IN A FINAL RULING, RELATED TO THE SERVICE, OR ANY OTHER OFFENCE THAT CAUSES SERIOUS DAMAGE TO THE ADMINISTRATION, CITIZENS OR LEGAL ENTITIES”. Supreme Court Ruling 5th Chamber, 13 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.33 OF THE LORDGC, CONSISTING OF A “SERIOUS OFFENCE IN THE FULFILMENT OF PROFESSIONAL OBLIGATIONS”. Supreme Court Ruling 5th Chamber, 13 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.7 OF THE LORDGC, IN RELATION TO AN “ABUSE OF POWERS THAT CAUSES SERIOUS DAMAGE TO THE ADMINISTRATION”. Supreme Court Ruling 5th Chamber, 06 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.6 OF THE LORDGC, IN THE FORM OF “SERIOUS DISRESPECT TOWARDS SUPERIORS, COLLEAGUES, SUBORDINATES OR CITIZENS IN THE EXERCISE OF THEIR DUTIES, ON THE OCCASION OF THEIR DUTIES OR WHILE IN UNIFORM”. Supreme Court Ruling 5th Chamber, 06 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.33 OF THE LORDGC, IN THE FORM OF “SERIOUS NEGLIGENCE IN THE FULFILMENT OF PROFESSIONALS OBLIGATIONS AND ORDERS RECEIVED”. Supreme Court Ruling 5th Chamber, 06 July 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.7 OF THE LORDGC, IN RELATION TO AN “ABUSE OF POWERS THAT CAUSES SERIOUS DAMAGE TO THE ADMINISTRATION”. Supreme Court Ruling 5th Chamber, 20 June 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.9 OF THE LORDGC, IN THE FORM OF “ISSUING SERVICE REPORTS THAT DO NOT CONFORM TO REALITY OR DISTORT IT”. Supreme Court Ruling 5th Chamber, 15 June 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.5 OF THE LORDGC, IN THE FORM OF “LACK OF SUBORDINATION”. Supreme Court Ruling 5th Chamber, 09 June 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.4 OF THE LORDGC, IN THE FORM OF “ANY ACTION THAT INVOLVES GENDER-BASED HARASSMENT”. Supreme Court Ruling 5th Chamber, 08 June 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.6 OF THE LORDGC, IN THE FORM OF “SERIOUS DISREGARD FOR SUBORDINATES IN THE EXERCISE OF THEIR FUNCTIONS”. Supreme Court Ruling 5th Chamber, 08 June 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.33 OF THE LORDGC, IN THE FORM OF “SERIOUS NEGLIGENCE IN THE FULFILMENT OF ORDERS RECEIVED”. Supreme Court Ruling 5th Chamber, 08 June 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.6 OF THE LORDGC, IN THE FORM OF “SERIOUS DISRESPECT TOWARDS SUPERIORS, IN THE EXERCISE OF THEIR DUTIES, AS PART OF THEIR DUTIES OR WHILE IN UNIFORM”. Supreme Court Ruling 5th Chamber, 19 May 2022 OFFENCE PROVIDED FOR IN ARTICLE 9.1 OF THE LORDGC, IN THE FORM OF "DISREGARD FOR SUPERIORS IN THE EXERCISE OF THEIR FUNCTIONS OR ON THE OCCASION THEREOF". Supreme Court Ruling 5th Chamber, 18 May 2022 OFFENCE PROVIDED FOR IN ARTICLE 7.23 OF THE LORDGC, IN THE FORM OF “RENDERING SERVICE IN A STATE OF DRUNKENNESS OR UNDER THE EFFECTS OF NARCOTICS OR TOXIC OR PSYCHOTROPIC SUBSTANCES OR THE CONSUMPTION THEREOF DURING THE SERVICE”. Supreme Court Ruling 5th Chamber, 11 May 2022 MINOR OFFENCE PROVIDED FOR IN ARTICLE 9.3 OF THE LORDGC, CONSISTING OF “NEGLIGENCE OR INACCURACY IN THE FULFILMENT OF ORDERS RECEIVED”. Supreme Court Ruling 5th Chamber, 04 May 2022 MINOR OFFENCE PROVIDED FOR IN ARTICLE 9.3 OF THE LORDGC, CONSISTING OF “INACCURACY IN THE FULFILMENT OF ORDERS RECEIVED”. Supreme Court Ruling 5th Chamber, 31 March 2022 OFFENCE PROVIDED FOR IN ARTICLE 8.33 OF THE LORDGC, CONSISTING OF A “SERIOUS OFFENCE IN THE FULFILMENT OF PROFESSIONAL OBLIGATIONS”. Supreme Court Ruling 5th Chamber, 17 February 2022.